Increased PD-1 Expression on Circulating T Cells Correlates with Inferior Outcome after Autologous Stem Cell Transplantation - Richter, Silja; Böttcher, Martin; Stoll, Andrej; Zeremski, Vanja; Völkl, Simon; Mackensen, Andreas; Ekici, Arif Bülent; Jacobs, Benedikt; Mougiakakos, Dimitrios (Transplantation and Cellular Therapy, 2024)
High-dose chemotherapy followed by autologous stem cell transplantation (auto-SCT) is a well-established treatment option for multiple myeloma and malignant lymphoma patients. It is able to induce long-term progression-free survival (PFS) in both patient groups and even provide a cure in patients with aggressive lymphoma. However, relapse is common and has been associated with the pace and quality of immunologic reconstitution after transplantation, as well as with immune cell exhaustion and immunometabolic defects. We aimed to analyze the dynamics of the prototypical exhaustion marker PD-1 on immune cells during reconstitution on high-dose chemotherapy followed by auto-SCT and its impact on PFS. We performed a comprehensive analysis of exhaustion and metabolic markers on immune cells from myeloma and lymphoma patients undergoing auto-SCT using flow cytometry and NanoString technologies. The expression levels of PD-1 were increased during early reconstitution after transplantation on T cells and natural killer (NK) cells, as well as on monocytes. However, while PD-1 expression in NK cells and monocytes normalized over time, PD-1 expression on T cells demonstrated a variable course. Of note, lymphoma patients with continuously increasing PD-1 expression on T cells after auto-SCT had an inferior median PFS of only 146 days, whereas the median PFS was not reached in the lymphoma patients without such a PD-1 expression pattern. T cells from patients with increased PD-1 expression after auto-SCT exhibited an immunometabolic (over)activation and exhausted phenotype compared to T cells from patients with a low PD-1 expression after transplantation, including higher levels of the glycolytic pacemaker enzyme hexokinase 2 and the inhibitory receptor CTLA-4. In addition, proliferating Ki-67+ T cells were more abundant in patients with high PD-1 expression on T cells compared to those with low expression after auto-SCT (11.9% versus 4.2%). PD-1 expression on T cells might serve as an adverse biomarker for lymphoma patients undergoing auto-SCT; however, further validation by larger prospective studies is required.
CRIS-Team Scopus Importer:2024-04-12
Keywords: auto-SCT; exhaustion; PD-1; T cells